CLASSIFICATION OF THE CELERY FAMILY APIACEAE LINDL. 1836 (UMBELLIFERAE JUSS. 1789) IN MONGOLIA - M, Urgamal (Proceedings of the Mongolian Academy of Sciences, 2017)
The classification position of Celery family Apiaceae Lindl. (Umbelliferae Juss.) in Mongolia is revised here. 76 species and 39 genus are included in this family. Also distribution data each species of this family in Mongolia are given.